Los profesores y la vida cívica de las escuelas - Hansen, David T. (Revista Española de Pedagogía, 2018)
Teachers can influence their students¿ moral and civic learning in two broad ways. The first is through deliberate, planned activities. These include organizing school-wide assemblies on the importance of voting, escorting students to visit political institutions, and sponsoring debates in the classroom on historical or current political issues. However, such activities are intermittent and discrete. They stand out and apart from the everyday business of teaching and learning in schools and classrooms. This daily business gives rise to the second way in which teachers can influence their students¿ moral and civic learning. Teachers can do so through what scholars have called their everyday manner, style, or tact of teaching. Each of these concepts describes a kind of teacher influence that is continous, ongoing, indirect, and often nonselfconscious and unplanned. The concepts spotlight the importance of the spirit in which the teacher works. That spirit can be more important, with respect to moral and civic learning, than curricular and instructional approaches considered by themselves. In this article, I examine the spirit of teaching and its importance for civic education by constructing composite images of two different classrooms. The two teachers I describe share a strong knowledge base in their discipline and are dedicated to their work. However, the spirit in which they teach differs markedly. As a result, while their students end the academic year performing comparably on their subject matter examinations, the students take away quite different moral and civic lessons from their classroom experience. I conclude the discussion by reminding teachers of the value of pondering their manner, style, and tact. I also urge schools to provide teachers systematic opportunities to discuss together the moral and civic dimensions of their everyday work.
Keywords: profesores; vida cívica; escuelas; Revista Española de Pedagogía